TEO-EKOLOGI BERBASIS NILAI LOKAL DALAM CITA HUKUM MASYARAKAT SUMBAWA - Lahmuddin Zuhri (Universitas Widya Gama Malang, 2019)
Pancasila (five basic principles) serves as the way of life of Indonesian people its first principle regulates the divine values and it is in line with kerik salamat (safety and blessing) which manifests the Islamic values in the cultures and custom in Sumbawa. Kerik salamat is Islamic values living in the society since it is a mirror of the ideal of cultural law of the society. In the nation spirit theory, a law should be born from the nation/society spirits. Good quality regulations should posses three basic principles: juridical, sociological, and philosophical. The value of kerik salamat from an Islamic epistemological dimension spreads in the whole life of the community so that their level of religiousity, karabat (kinship) and saling sating (respect one another) may be maintained sustainably by the people of Sumbawa. Kerik salamat as a norm of life in people of Sumbawa should be recognized and protected because it is a morror of the ideal of law of the people to maintain a harmony so that the value og kinship, and respect among the members of the people may be maintained to keep the oneness and togatherness and also the shame culture (ila). Thi guides them in a strong social tie and legal construction which is full of the values of kinship to keep the existence of the community, and the life pattern in line with the expectation of Gods blessings in the ideal of the law in the people of Sumbawa.